Mechanism-Driven Design of Multispecific Antibodies for Targeted Disease Treatment - Justyn Fine; Bunyarit Meksiriporn; Jiacheng Tan; Jamie B. Spangler (Annual Review of Chemical and Biomolecular Engineering, 2024)
, Volume 15 is June 2024. Please see http://www.annualreviews.org/page/journal/pubdates for revised estimates.
Keywords: Monoclonal and Polyclonal Antibodies Research; Protein purification and stability; CAR-T cell therapy research